Lessons learnt from the global iodinated contrast media shortage in head and neck imaging. Issue 8 (20th September 2022) - Fiori, Timothy; Lisewski, Dean; Flukes, Stephanie; Wood, Chris; Gibson, Daren
Summary: A recent shortage in the global supply of iodinated contrast media (ICM) has required health service providers to review their contrast administration policies and implement strategies to conserve inventory. This article will review the current best practices in head and neck imaging for a variety of common presentations and provide examples where alternative imaging can be considered due to the recent ICM shortage. Ultrasound and MRI techniques can feature heavily in many diagnostic processes in head and neck pathology, and a variety of common presentations can be appropriately investigated through clinical evaluation or naso‐endoscopy. In many instances, for the routine assessment of non‐acute adult and paediatric head and neck presentations, the use of contrast‐enhanced CT can be safely minimised to conserve ICM if required.